Eurocommunism : the Italian case - Ranney, Austin; Sartori, Giovanni (Washington : American Enterprise Institute for Public Policy Research, 1978)
Econommunism, as manifested in the current statements and activities of the French, Italian, and Spanish Communist parties, represent a genuine break with Soviet-style Marxism-Leninism, or is it a new stratagem to bring down Western democracy?
Based on conference held in Washington, D.C., June 7-9, 1977.
Includes bibliographical references.
usc 13/02/2019
Loans
Keywords: Communism; Communist parties